Feminisme of the Main Character in The Girl on the Train Movie - Furi Indriyani; Endah Sofyan; Nurmala Dewi; Tati Mardewi (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Feminism is a women's movement in seeking equality to be equal to men in any way, including relationships. In this study, the writers’ purpose of analyzing The Girl on the Train movie is to find out the kind of feminism, the causes of feminism that influence the main character, and the moral message contained in the movie. The writers use qualitative research methods in describing and analyzing this movie. The writers also do library research to find many references from books or the internet which are useful to support this paper, especially the theories. After analyzing the movie, the writers found one of four kinds of feminism which is Liberal Feminism. Liberal feminism is women's liberation about certain aspects of themselves or their lives. They claim that women have the same capacities as men, and have the same rational thinking as men. Another result, there are also two causes of feminism that influence the main character in this movie, namely betrayal, and domestic abuse. Besides that, this movie sends moral messages. This movie tells about women who are treated unfairly and experience many painful things in the relationship. The women must dare to defend themselves and fight men who are cruel to them. And every woman will help another woman in any situation, even if it threatens her.